The Effect Of Banana Skin Flour Substitution On The Quality Of The Cupcake - Kimara, Yolla Fiscilia; Holinesti, Rahmi (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
This study aims to analyze the quality of cupcakes from banana peel flour as much as 15%, 30%, and 45%. This research was conducted at the culinary arts workshop majoring in family welfare science in August 2021. This type of research was experimental using a Completely Randomized Design (CRD) consisting of 3 treatments and 3 repetitions. Data analysis was obtained from Organoleptic Test involving 5 expert panelists. The data obtained were then analyzed using the ANOVA method, if there was a significant effect, it would be continued with Duncan's test. The results showed that banana peel flour substitution affected blackish brown color, banana aroma, and sweet taste. Which does not affect shape and texture. Based on the results of the research, the best shape quality (symmetrical round) cupcake was with X3 treatment with a score of 3.53, the best shape quality (neat) cupcake with X3 treatment with a score of 3.53, the best color quality (dark brown) cupcake with X3 treatment with a score of 3.80, the best aroma quality (banana) cupcake with X3 treatment with a score of 3.47, the best texture (soft) quality cupcake with X1 treatment with a score of 3.47, the best taste (sweet) cupcake with X1 treatment with a score of 3, 60, very suitable for consumption. So for further research, it is recommended that the use of banana peel flour should be as much as 45%, namely by treatment (X3).